|Harm harness harmony| - Kenny, Michael, author; Beachy-Quick, Dan, advisor; Steensen, Sasha, advisor; Fassnacht, Steven, committee member (Colorado State University. Libraries, 2014)
A single agent perceiver explores the arctic self via four elemental forms.
Harm harness harmony
Keywords: poetry; Iditarod